Genetic dissection of vitamin E biosynthesis in tomato - Almeida de Souza, Juliana Beatriz (2011)
Vegetables are critical for human health as they are a source of multiple vitamins including vitamin E (VTE). In plants, the synthesis of VTE compounds, tocopherol and tocotrienol, derives from precursors of the shikimate and methylerythritol phosphate pathways. Quantitative trait loci (QTL) for α-tocopherol content in ripe fruit have previously been determined in an Solanum pennellii tomato introgression line population. In this work, variations of tocopherol isoforms (α, β, γ, and δ) in ripe fruits of these lines were studied. In parallel all tomato genes structurally associated with VTE biosynthesis were identified and mapped. Previously identified VTE QTL on chromosomes 6 and 9 were confirmed whilst novel ones were identified on chromosomes 7 and 8. Integrated analysis at the metabolic, genetic and genomic levels allowed us to propose 16 candidate loci putatively affecting tocopherol content in tomato. A comparative analysis revealed polymorphisms at nucleotide and amino acid levels between Solanum lycopersicum and S. pennellii candidate alleles. Moreover, evolutionary analyses showed the presence of codons evolving under both neutral and positive selection, which may explain the phenotypic differences between species. These data represent an important step in understanding the genetic determinants of VTE natural variation in tomato fruit and as such in the ability to improve the content of this important nutriceutical.